EVALUASI PROGRAM PENDIDIKAN PESANTREN MAHASISWA MODEL CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) - Walid Fajar Antariksa; Abdul Fattah; Mutiara Arlisyah Putri Utami (STAI Ma'had Aly Al-Hikam Malang, 2022)
Pesantren is an educational institution in Indonesia that focuses on developing the religious character of its students. Pesantren has developed into various types, one of which is student boarding schools. Pesantren as educational institutions need to evaluate their educational programs to measure the extent of their effectiveness in achieving goals. One of the methods that are often used in the evaluation is the CIPP (Context, Input, Process, Product) model. This study aims to evaluate the student boarding school education program with the CIPP model. The location of this research is at the Student Islamic Boarding School of UIN Maulana Malik Ibrahim Malang. The method used is qualitative and quantitative. Data collection techniques using observations, interviews, documentation, and questionnaires. The results showed that the evaluation of the context aspect, in general, was effective, the evaluation of the input aspect was considered quite effective, the evaluation of the process aspect still needed to be improved, while the evaluation of the product aspect was considered to be lacking.